Sequence modeling in zircon double-dating of early Holocene Mt. Erciyes domes (Central Anatolia) - Friedrichs, Bjarne; Atıcı, Gokhan; Danišík, Martin; Yurteri, Esra; Schmitt, Axel Karl (Quaternary geochronology, 2021)
Mt. Erciyes (3917 m), the highest stratovolcano in Central Anatolia, Turkey, is considered active based on three recently dated early Holocene dome eruptions that were also correlated with tephras in the Mediterranean and the Black Sea. Despite the demonstrated Holocene activity of Mt. Erciyes, the eruptive chronostratigraphy of these events and their hazard potential for the nearby Kayseri metropolitan area (population ~1.4 million) remain poorly constrained. Here, we apply zircon double-dating (ZDD) based on (U-Th)/He thermochronology and U-Th-Pb crystallization ages, where intra-grain crystallization age differences were used for disequilibrium correction. Individual ZDD ages were refined via sequence modeling to reconstruct the eruption timing of four early Holocene domes peripheral to Mt. Erciyes. Sequence modeling, which incorporated petrological, volcanological, and stratigraphic constraints, yielded the following eruption ages (uncertainties stated at 1σ): 8.8 ± 0.8 ka for stratigraphically directly superimposed Perikartın and Karagüllü, 8.9 ± 0.5 ka for Dikkartın, and 9.4 ± 1.3 ka for previously undated Yılanlı Dağ, located within the perimeter of Kayseri. A model where all four early Holocene domes are assumed to have erupted simultaneously suggests an age of 8.9 ± 0.4 ka. Earlier eruptive phases of Mt. Erciyes were identified by ZDD at ca. 85-88 ka (fall-out deposits and Çarik Tepe lava) and at ca. 105 ka (xenoliths from two peripheral scoria cones). Zircon crystallization ages reveal protracted magmatic activity beneath Mt. Erciyes since ca. 800 ka, in agreement with dated volcanic activity, and preceding magmatic phases at ca. 2-3 Ma that included the eruption of the widespread Valibaba Tepe Ignimbrite with a U-Pb zircon age of 2.73 ± 0.02 Ma. A volume estimate for the Quaternary edifice of ~300 km3 translates into an integrated long-term eruptive magma flux of ~0.4 km3/ka for post-collisional Mt. Erciyes, within uncertainty of the Late Pleistocene-Holocene flux estimate of >0.1 km3/ka based on dome volumes and eruption ages. The near-synchronous eruptions of a suite of four evolved domes, in three cases with sizable early explosive venting, calls for a hazard assessment that combines the impact of multiple simultaneous eruptions.
Gesehen am 08.02.2021
Available online 11 October 2020